Writing for Healing: Program Peningkatan Kesehatan Mental Mahasiswa Wilayah Semarang - Mulawarman; Hariyadi, Sigit; Kurniawan, Kusnarto; Rizqia Azhar, Nailah; Belva, Edgina; Ayu Setiyawati, Dewi (Jurnal Inovasi Pengabdian Masyarakat, 2024)
Everyone must experience problems, and everyone must have had problems, because problems teach a person to be more mature. The form of individual expression when facing problems is different. Some isolate themselves from the crowd and other people, meet other people for example counselors just to tell what disturbs their thoughts, feelings and self. However, there are also those who write down every incident and event that disturbs their thoughts, feelings and self as a diary, then immortalize it as a diary or diary as a form of expression. Therefore, this community service activity generally aims to help counselees strengthen their capacity in undergoing life problems through a series of mentoring activities for counselees in Peer Counselor Community. This community service activity can empower the counselee to keep struggling in his life path. The method of implementing this service starts from (1) preparation, (2) preparation of materials, (3) introduction, (4) training, (5) closing, and (6) reporting. Technical data analysis used using SPSS 26 using the Wilcoxon test to determine differences in mental health conditions before and after training. The results of the implementation of the service that there is an effect of writing for healing training to improve students' mental health.